The Tradition of Postponing Cohabitation until Walimatul ‘Ursy in Cerenti: Durkheim’s solidarity analysis - Musdalifa, Musdalifa; Riyadi, Alif Andaru; Rahmayani, Rahmayani; Nisa, Khoirun; Syahid, Abdur Rahman (el Harakah: Jurnal Budaya Islam, 2025)
Marriage customs in Malay communities continue to evolve amid shifting social values, yet scholarly attention to how local traditions mediate the relationship between Islamic law and indigenous norms remains limited. Although various studies have examined marriage rituals in Indonesia, no research has specifically analyzed the tradition of postponing cohabitation until the walimatul ‘ursy in Cerenti District, nor how this custom functions as a socio-religious mechanism that maintains communal harmony. This gap highlights the urgency of investigating how the practice negotiates the potential tension between Islamic permissibility for immediate cohabitation and customary restrictions rooted in Malay moral philosophy. Its novelty lies in analyzing Malay marriage traditions through the perspective of social cohesion, demonstrating how local and religious values interact in shaping social order. This study discusses the tradition of postponing cohabitation until walimatul ‘ursy (wedding celebration) in the Malay community in Cerenti District as a socio-religious practice that reflects the balance between Islamic customs and sharia, and functions as a social mechanism that strengthens community cohesion. The purpose of the research is to analyze the social function and religious value of the tradition through Emile Durkheim's theory of social solidarity. The research uses a qualitative approach with field data through in-depth interviews with four indigenous figures, data analysis is carried out descriptive-analytically using Durkheim's concept of mechanical and organic solidarity. The results of the study show that postponing cohabitation serves as a mechanism of self-control, family respect, and guardian of the sanctity of marriage. These findings confirm that the tradition strengthens social unity through the common values and collective norms of the Cerenti community. Practically, this research provides insights applicable to family development and the preservation of customs based on Islamic values. In conclusion, this tradition does not restrict individuals freedom but plays a role in maintaining the moral and social balance of the community. Tradisi pernikahan dalam masyarakat Melayu terus mengalami dinamika seiring perubahan nilai sosial, namun kajian ilmiah mengenai bagaimana adat lokal memediasi hubungan antara hukum Islam dan norma budaya masih terbatas. Meskipun sejumlah penelitian telah membahas ritual pernikahan di Indonesia, belum ada studi yang secara khusus menganalisis tradisi penundaan tinggal bersama hingga pelaksanaan walimatul ‘ursy di Kecamatan Cerenti, maupun bagaimana praktik tersebut berfungsi sebagai mekanisme sosial-keagamaan yang menjaga keharmonisan komunal. Kekosongan kajian ini menunjukkan urgensi untuk menelusuri bagaimana tradisi tersebut merundingkan potensi ketegangan antara kebolehan syariat untuk langsung tinggal bersama dan pembatasan adat yang berakar pada filosofi moral masyarakat Melayu. Kebaruan penelitian terletak pada analisis tradisi pernikahan Melayu melalui perspektif kohesi sosial yang menunjukkan bagaimana nilai lokal dan religius berinteraksi dalam membentuk ketertiban sosial. Penelitian ini membahas tradisi penundaan tinggal bersama hingga walimatul ‘ursy pada masyarakat Melayu di Kecamatan Cerenti sebagai praktik sosial keagamaan yang mencerminkan keseimbangan antara adat dan syariat Islam, serta berfungsi sebagai mekanisme sosial yang memperkuat kohesi masyarakat. Tujuan penelitian adalah menganalisis fungsi sosial dan nilai religius tradisi tersebut melalui teori solidaritas sosial Emile Durkheim. Penelitian menggunakan pendekatan kualitatif dengan data lapangan melalui wawancara mendalam dengan empat tokoh adat, analisis data dilakukan secara deskriptif-analitis dengan menggunakan konsep solidaritas mekanik dan organik Durkheim. Hasil penelitian menunjukkan bahwa penundaan tinggal bersama berfungsi sebagai mekanisme pengendalian diri, penghormatan keluarga, dan penjaga etika kesucian pernikahan. Temuan ini menegaskan bahwa tradisi tersebut memperkuat kesatuan sosial melalui kesamaan nilai dan norma kolektif masyarakat Cerenti. Secara praktis, penelitian ini memberikan wawasan yang dapat diterapkan dalam pembinaan keluarga dan pelestarian adat berbasis nilai Islam. Kesimpulannya, tradisi ini tidak membatasi kebebasan individu, tetapi berperan menjaga keseimbangan moral dan sosial dalam komunitas..